Potential Role of Prenatal Inflammation in the Impairment of Lung Development Following Mechanical Ventilation of Preterm Lambs. (March 2017) - Hanita, Takushi; Matsuda, Tadashi; Saito, Masatoshi; Kitanishi, Ryuta; Cho, Kazutoshi; Harding, Richard; Kobayashi, Yoshiyasu
Background: Our objective was to determine the effects of severe fetal inflammation, associated with an increase in the number and activation state of fetal polymorphonuclear leukocytes (PMNLs), on postnatal lung development in mechanically ventilated preterm lambs. Methods: Four groups of preterm fetal sheep (0.85 term) were surgically prepared: (1) a granulocyte-colony stimulating factor (GCSF) group received intravenous GCSF to increase fetal PMNL count, (2) a lipopolysaccharide (LPS) group received intra-amniotic LPS to activate the fetal PMNLs, (3) a GCSF + LPS group received both GCSF and LPS, and (4) a control group received saline. After 10-day mechanical ventilation following preterm delivery, the lungs were examined histologically and analyzed morphometrically. Results: Compared to the control group, the GCSF + LPS group exhibited necrotizing funisitis, lower surface density of alveolar walls, lower numerical density of alveoli, greater alveolar radius, and lower volume density of secondary septal crests (all P < .05). There was no evidence of tissue destruction, or elastin fragmentation or thick deposits of elastin, in the alveolar walls in any of the 4 groups. Conclusion: The mechanical ventilation following severe prenatal inflammation did not lead to overt lung injury or degradation of elastin but resulted in arrested alveolarization in the lungs of preterm lambs.